Run for your life [videorecording (DVD)] - Ehrlich, Judd; Ehrlich, Judd; Rodgers, Bill, 1947-; Salazar, Alberto, 1958-; Shorter, Frank, 1947-; Waitz, Grete, 1953-2011 (Screen Media Films, 2008)
Learn how one immigrant's determination created the world's most significant running event. It touches the heart and soul of anyone with a passion for running, and documents the inspirational life of Fred Lebow and the history of the New York City Marathon.